PENINGKATAN KUALITAS GURU AL QUR’AN DALAM PROSES BELAJAR MENGAJAR MELALUI SERTIFIKASI METODE UMMI - Ahmad Bukhori S (Jurnal Penelitian Ilmiah INTAJ, 2022)
The need for schools and madrasas for good teaching of the Qur'an is felt to be increasing day by day. What we should be grateful for, however, this need has not been matched by the availability of human resources (HR) for Al-Qur'an teachers who have competence and commitment in the field of adequate Al-Qur'an learning. Good learning to read the Koran requires a system that is able to guarantee the quality of every child or person who learns to read the Koran so that it is quick and easy to read the Koran tartīl. And as with other learning programs, learning the Qur'an also requires development, both in terms of content, context and support system. In realizing the above, the Ummi Foundation has built a quality system for learning the Qur'an by standardizing its input, process and output. the entire standardization is summarized in 7 (seven) basic Ummi programs, which include: tashhīh, tahsīn, certification, coach, supervision, munāqasyah, and khataman. Certification is one of the seven basic programs which is an absolute requirement for a teacher who will teach the Ummi Method. Without teacher certification, Ummi's book becomes meaningless and loses its strength as an easy, fast, and quality method and loses its soul as a fun and heart-touching method.